TIME COST TRADE OFF ANALYSIS ON PROJECT ACCELERATION WITH ADDITIONAL WORKING HOURS (OVERTIME) (CASE STUDY: BUILDING REHABILITATION PROJECT ON DEKRANASDA HALL OF WEST KALIMANTAN) - Azzahra, Yasra; Lusiana, Lusiana; Rafie, Rafie; Syahrudin, Syahrudin; Nuh, Safaruddin M. (Fakultas Teknik Universitas Tanjungpura, 2023)
Acceleration on projects is frequently used when there is a mismatch between the actual and planned schedules. In addition, acceleration is frequently implemented in response to requests from the project owner to complete the project as quickly as possible to meet specific goals so that the building can be used immediately. The owner of the Dekranasda Building and Hall in West Kalimantan requested that the project be finished immediately so that the Dekranasda Building could be used as the location for a national UMKM exhibition event. The initial plan for this project was scheduled for 152 working days. Because there would be an exhibition event, the project was accelerated to 128 working days. The purpose of this research is to accelerate the project for 24 days. The stages of this acceleration analysis start from finding what activities can be softened, then compiling a network diagram to identify activities on the critical path, followed by crashing analysis to get crash duration, crash cost, and cost slope, then Time Cost Trade-Off analysis is carried out. This research uses the PDM (Precedence Diagram Method) method applied to Microsoft Project to compile a Network Diagram. The results of the acceleration analysis show that the crashing process is carried out until the 12th crashing to meet the target acceleration duration of 128 working days from the normal duration of 152 working days, and the usual 24-day length is shortened. Twelve tasks have been added, raising the overall project cost from Rp. 6,794,007,874 to Rp. 7,091,725,614 by a total of Rp. 297,717,741.